Sexual Polarities: Shelley’s Frankenstein and Polar Exploration as a Search for Origins Beyond ‘woman’ - Gould, Polly (Nordlit, 2008)
This paper is about our parents and our predecessors in life and in literature. It specifically interrogates the choice of Polar landscapes for the playing out of narratives of gender difference in stories of Arctic and Antarctic exploration. I have chosen to pay attention to three narratives: Shackleton’s South, Mary Shelley’s Frankenstein and Ursula Le Guin’s short story Sur. They all take place in the icy expanse of the Arctic and Antarctic. I will read them in the light of the question of origins: ‘where do I come from?’